(untitled) (The Planet, 2025)
Introduction: Cataract surgery is one of the most commonly performed procedures worldwide, aimed at restoring vision in patients with age-related cataracts. The two primary techniques used in cataract surgery are phacoemulsification (phaco) and manual small incision cataract surgery (MSICS). This study is designed to evaluate and compare the clinical outcomes of phacoemulsification and MSICS in age-related cataract patients. Methods & Materials: This prospective, comparative, randomized controlled study aimed to evaluate the outcomes of phacoemulsification versus manual small incision cataract surgery (MSICS) in 90 patients with age-related cataracts. The study took place in the Department of Ophthalmology, at Ispahani Islamia Eye Institute & Hospital, Dhaka, Bangladesh, from July 2023 to January 2024. A total of 90 patients were randomly assigned to either the phacoemulsification group (n=45) or the MSICS group (n=45). Statistical analysis was performed using SPSS version 23.0. Result: Phacoemulsification had a significantly better postoperative visual acuity at multiple time points: on day 1 post-op (0.43 ± 0.12 vs. 0.49 ± 0.15, p=0.03), 1-week post-op (0.21 ± 0.09 vs. 0.26 ± 0.10, p=0.01), and 6 weeks post-op (0.10 ± 0.05 vs. 0.13 ± 0.06, p=0.02) compared to MSICS. Surgically induced astigmatism (SIA) was lower in the phacoemulsification group, with a mean SIA of 0.65 ± 0.32 D compared to 1.15 ± 0.46 D in MSICS (p<0.001). Conclusion: This study shows that phacoemulsification offers superior postoperative visual outcomes and less surgically induced astigmatism compared to MSICS. Both techniques provide good visual results, making MSICS a viable alternative in resource-limited settings.